PEMBELAJARAN TARI TRADISIONAL DI ERA DIGITAL: STUDI NARATIF TERHADAP PRAKTIK GURU SMA N 16 SEMARANG YANG MENGINTEGRASIKAN YOUTUBE DI KELAS - Kejora Hatrikapaksi, Giyang; Rimasari Pramesti Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The digital age has brought about significant transformations in the world of education, including in the teaching of traditional dance. This study aims to conduct a narrative analysis of the practices of a teacher at State Senior High School 16 in Semarang in integrating the YouTube platform as a medium for teaching traditional dance in the classroom. Using a qualitative approach and narrative study methods, data were collected through classroom observations, in-depth interviews, and documentation. The results show that the use of YouTube not only increases student engagement in the learning process but also expands their access to various references on traditional dance from different regions. The teacher utilizes dance videos as learning resources, assessment tools, and a means for student self-reflection. The integration of YouTube also facilitates more flexible and contextual learning, although it still faces challenges such as limited internet access and digital literacy skills. This study recommends enhanced training for teachers in the use of technology as well as the development of high-quality digital content for arts and culture education.